The symbolic meaning of the number of days mentioned in the book of Jonah - Schäder, Jo-Marí (HTS teologiese studies, 2020)
The book of Jonah uses four indications of time: (1) Jonah spends 3 days and three nights in the fish; (2) the city of Nineveh takes 3 days to cross; (3) Jonah enters the city to the extent or distance of one day’s travel; and (4) Jonah proclaims to Nineveh that she has 40 days to repent. In this article it will be pointed out that each of the four instances where time is mentioned in the book of Jonah has a symbolic meaning and intends to mean more than is evident on the surface of the text.Contribution: This article contributes to the ongoing critical scholarship of the book of Jonah. In this article the interpretation of time in relation to the number of days mentioned in the book of Jonah is revisited and it is argued that the days should be understood symbolically and not literally. An evaluation is also given of what their meanings are.